1989
DOI: 10.2190/kw8y-f816-bfvn-lqqb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-Simulated Behavior Analysis on Pre-Service Teachers' Problem Solving

Abstract: Undergraduate students ( n = 64) enrolled in an educational psychology course were randomly assigned to groups (computer simulation, extended-instruction, problem solving, and control) to practice behavior management principles related to classroom problems. On the main dependent measure, applied problem-solving, the computer simulation group was the only group to show significantly higher level of performance on the total measure over the control group. For the targeted subskills within the applied measure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…No change was made in their ability to involve students. Gorell and Downing (1989) completed an experimental study to determine if a computer simulation was best at helping students learn to analyze classroom behaviors for solving problems. While the results did show the simulation group used analysis skills more often, no improvement on knowledge or self-efficacy was found.…”
Section: The Value Of Simulating Classroom Behaviormentioning
confidence: 99%
“…No change was made in their ability to involve students. Gorell and Downing (1989) completed an experimental study to determine if a computer simulation was best at helping students learn to analyze classroom behaviors for solving problems. While the results did show the simulation group used analysis skills more often, no improvement on knowledge or self-efficacy was found.…”
Section: The Value Of Simulating Classroom Behaviormentioning
confidence: 99%
“…Taylor (2009) stated that classroom teaching affected student achievement more than other activities that did in the classroom; quality classroom teaching required quality classroom management skills. Gorrell and Downing (1989) found that computer simulations were best at helping students learn to analyze phenomena and solve problems. Kuh, Cruce, Shoup, Kinzie, and Gonyea (2008) suggested that students" success closely linked with students" academic achievement in educational focusing activities: attaining of preferred knowledge, learning skills and capabilities, achieving educational objectives and having post-college performance in real life.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor (2009) stated that classroom teaching affected student achievement more than other activities that did in the classroom; quality classroom teaching required quality classroom management skills. Gorrell and Downing (1989) found that computer simulations were best at helping students learn to analyze phenomena and solve problems. Kuh, Cruce, Shoup, Kinzie, and Gonyea (2008) suggested that students" success closely linked with students" academic achievement in educational focusing activities: attaining of preferred knowledge, learning skills and capabilities, achieving educational objectives and having post-college performance in real life.…”
Section: Discussionmentioning
confidence: 99%